Concept assessment and revitalization the level of innovation state of industrial enterprises - I. A. Goncharova (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2016)
Development of the corresponding scientific approaches and concepts is necessary for the solution of an actual problem of definition of the priority directions and actions for innovative development of the industrial enterprise. The concept of an assessment and activization of an innovative state offered by the author assumes formation of reasonable recommendations about stimulation of level of an innovative condition of the industrial enterprise on the basis of a complex of consistently carried out actions within three main units. The block I «Analysis of prerequisites for an assessment and stimulation of level of an innovative condition of the enterprise» is introduction and is intended for determination of introduction parameters of the carried-out assessment. Within the block II «Definition of internal state of the enterprise» the relevant system of indicators is developed for an assessment of level of an innovative state at the microlevel by means of analogies between physical and economic quantities. Important stage of the block II is the analysis of an intra-branch innovative state which is made by means of the system of a comparative assessment of level of an innovative condition of the industrial enterprise developed by the author. The specified system allows to determine quickly the level of an innovative condition of the enterprise and on the basis of low values of criteria to create the main directions of perspective development. The method of Delfi with a parallel assessment of the analyzed and reference organization is the basis for this system. Formation of indicators and indicators of level of an innovative condition of the analyzed and reference organization is made by means of mathematical linear regressions therefore the coefficient of comparison of level of an innovative condition of the analyzed and reference organizations is defined. Total conclusions and complex of the corresponding practical recommendations about stimulation of level of an innovative condition of the analyzed enterprise are defined within the block III taking into account an assessment of extent of influence of external factors and the third-party organizations on the level of innovative development.